Catastrophic Medical Expenditure Risk - Gabriela Flores; Owen O'Donnell (Center for Economic Studies and ifo Institute (CESifo), 2013)
Medical expenditure risk can pose a major threat to living standards. We derive decomposable measures of catastrophic medical expenditure risk from reference-dependent utility with loss aversion. We propose a quantile regression based method of estimating risk exposure from cross-section data containing information on the means of financing health payments. We estimate medical expenditure risk in seven Asian countries and find it is highest in Laos and China, and is lowest in Malaysia. Exposure to risk is generally higher for households that have less recourse to self-insurance, lower incomes, wealth and education, and suffer from chronic illness.
Keywords: D12; D31; D80; I13; I15; 330; medical expenditures; catastrophic payments; downside risk; reference-dependent utility; Asia